Electrode assembly and lithium secondary battery comprising same

By using a coating containing oxide solid electrolyte particles, polymer particles and ceramic particles in lithium secondary batteries, the problems of short circuit and fire in lithium secondary batteries in high temperature environments are solved, and the electrolyte impregnation is improved, improving improved battery performance.

CN119343799APending Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380045445.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-20
Filing Date
2023-12-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing lithium secondary batteries are prone to short circuits and fires in high temperature environments, and the flame-retardant electrolyte cannot be effectively immersed into the separator, resulting in deterioration of battery performance.

Method used

The coating containing oxide -like solid electrolyte particles, polymer particles and ceramic particles is located between the positive and negative electrodes to improve the high temperature safety and electrolyte impregnation of the battery.

Benefits of technology

Effectively prevent the short circuit between the positive and negative electrodes, improve the high temperature safety of the lithium secondary battery, and improve the capacity, output and life characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343799A_ABST
    Figure CN119343799A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode assembly comprising a positive electrode, a negative electrode, and a coating layer between the positive electrode and the negative electrode, in which the coating layer contains (a) oxide-based solid electrolyte particles and (b) one or more selected from the group consisting of polymer particles and ceramic particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0181062, filed on December 21, 2022, and Korean Patent Application No. 10-2023-0187353, filed on December 20, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to an electrode assembly and a lithium secondary battery including the same. [Background Technology]

[0004] Recently, as the application fields of lithium secondary batteries have rapidly expanded to energy storage power sources for large-area devices such as automobiles and power storage devices, as well as power sources for electronic equipment such as electricity, electronics, communications and computers, the demand for lithium secondary batteries with high capacity, high output, long life and high stability has increased.

[0005] Typically, a lithium secondary battery consists of a positive electrode, a negative electrode, a separator interposed between the two electrodes, and an organic solvent. Because the positive electrode is structurally unstable when charged and generates oxygen, which poses a high risk of fire, researchers have been researching and developing methods to improve the safety of lithium secondary batteries.

[0006] A separator is used to ensure electrical insulation between the positive and negative electrodes, typically using a film made of polyolefin. However, polyolefin separators tend to shrink in high-temperature environments, making it impossible to insulate the positive and negative electrodes. When electrical insulation between the positive and negative electrodes fails, a short circuit can occur, which can interact with oxygen generated by the unstable positive electrode, leading to a fire. In other words, when a short circuit occurs in a charged lithium secondary battery in a high-temperature environment, there is a risk of the battery catching fire.

[0007] Furthermore, it is well known that the electrolyte of a lithium secondary battery contains a highly volatile and flammable solvent, and thus has the problem of being easily ignited.

[0008] To address this issue, flame-retardant electrolytes containing flame-retardant solvents can be used. However, this type of electrolyte cannot be properly impregnated into conventional separators. If the electrolyte cannot be properly impregnated into the lithium secondary battery, lithium ions cannot be properly transported, resulting in degradation of the battery's capacity, output, and lifespan. Furthermore, if the electrolyte cannot be properly impregnated into the lithium secondary battery, uneven reactions between the electrodes and the electrolyte can occur, leading to the formation of dendrites and resulting in short circuits.

[0009] Therefore, in order to solve these problems, people have attempted to research and develop methods for improving the stability of lithium secondary batteries while maintaining various performances. [Summary of the invention]

[0010] [Technical Issues]

[0011] Therefore, the present invention aims to solve the above problems, and an object of the present invention is to provide an electrode assembly that not only has excellent high-temperature safety to prevent fire, but also has high electrolyte impregnation and thus excellent battery performance, and a lithium secondary battery containing the same.

[0012] [Technical solution]

[0013] According to one embodiment of the present invention, there is provided an electrode assembly comprising:

[0014] positive electrode, negative electrode and coating between the positive electrode and negative electrode,

[0015] The coating layer contains (a) oxide solid electrolyte particles and (b) one or more selected from the group consisting of polymer particles and ceramic particles.

[0016] The oxide solid electrolyte particles may include one or more selected from the group consisting of: LLTO compounds, Li6La2CaTa2O 12 、Li6La2ANb2O 12 (where A is Ca or Sr), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 、Li9SiAlO8、LAGP compounds、LATP compounds、Li 1+x Ti 2-x Al x Si y (PO4) 3-y (where 0≤x≤1, 0≤y≤1), LiAl x Zr 2-x (PO4)3 (where 0≤x≤1), LiTi x Zr 2-x (PO4)3 (wherein 0≤x≤1), LISICON compounds, LIPON compounds, perovskite compounds, Nasicon compounds, LLZO compounds and LLZMO compounds.

[0017] Furthermore, the absolute values ​​of the zeta potentials of the polymer particles and the ceramic particles can each be greater than 25 mV.

[0018] The polymer particles may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0019] In addition, the ceramic particles may include one or more selected from the group consisting of boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, and MnO.

[0020] In this case, the content of the oxide-based solid electrolyte particles in the coating layer may be 10 wt % to 90 wt % based on the total weight of the coating layer.

[0021] Specifically, the coating may comprise (a) oxide solid electrolyte particles and (b) polymer particles, wherein the polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0022] That is, the coating layer may substantially contain oxide-based solid electrolyte particles and polymer particles. In addition, the coating layer may further contain one or more additives selected from the group consisting of a binder and a dispersant.

[0023] Furthermore, the coating may have a thickness of 3 microns to 30 microns.

[0024] Meanwhile, in one exemplary embodiment, the coating layer may be formed on the positive electrode or the negative electrode.

[0025] In this case, the electrode assembly further includes a separator, wherein the separator may be located between the positive electrode and the coating layer, or between the negative electrode and the coating layer.

[0026] Alternatively, in another exemplary embodiment, the coating layer may include a first coating layer formed on the positive electrode and a second coating layer formed on the negative electrode.

[0027] In this case, the electrode assembly further includes a separator, wherein the separator may be located between the first coating layer and the second coating layer.

[0028] Alternatively, in another exemplary embodiment, the electrode assembly further includes a separator, and the coating layer may be formed on one or both surfaces of the separator.

[0029] In this case, the separator may be an SRS separator having a structure in which an organic-inorganic hybrid layer containing inorganic particles and a binder is formed on one side or both sides of a substrate.

[0030] According to another embodiment of the present invention, there is provided a lithium secondary battery including an electrode assembly, an electrolyte, and a battery case.

[0031] In this case, the electrolyte may be a flame retardant electrolyte containing a flame retardant solvent and a lithium salt.

[0032] The flame retardant solvent may include one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorocarbonate compounds, and the lithium salt may include LiN(SO2CF3)2. [Brief Description of the Drawings]

[0033] Figure 1 An electrode assembly according to one embodiment of the present invention is schematically shown.

[0034] Figure 2 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0035] Figure 3 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0036] Figure 4 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0037] Figure 5 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0038] Figure 6 An electrode assembly according to another embodiment of the present invention is schematically shown. [Specific implementation method]

[0039] Hereinafter, the terms or words used in this specification and claims should not be understood as being limited to conventional terms or dictionary terms, but should be interpreted in the sense that they are consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his invention in the best possible manner.

[0040] Unless otherwise defined, all terms (including technical and scientific terms) used in this specification may have the meanings commonly understood by those skilled in the art to which the present invention belongs. In addition, unless otherwise clearly defined, terms defined in commonly used dictionaries should not be idealized or over-interpreted.

[0041] The terms used herein are used to describe embodiments but do not limit the concepts of the present invention. In the specification, unless the context clearly indicates otherwise, the singular includes the plural. The terms "comprise" and / or "include" as used herein do not exclude the presence or addition of one or more elements other than those described.

[0042] Throughout the specification, unless explicitly described to the contrary, the word “comprise” and variations such as “comprises” or “comprising”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.

[0043] As used herein, "zeta potential" is an indicator of the degree of surface charge on particles. For example, the zeta potential of the particles of the present invention can be measured by electrophoretic light scattering using a dynamic light scattering device. Specifically, the zeta potential of the polymer particles or ceramic particles contained in the coating of the present invention can be measured by electrophoretic light scattering using a dynamic light scattering device. For example, the zeta potential can be measured after dispersing the polymer particles or ceramic particles in a solvent such as water or alcohol without a dispersant.

[0044] Hereinafter, the embodiments described herein and the configurations shown in the accompanying drawings are merely the most preferred embodiments of the present invention and do not represent the entire spirit of the present invention. Therefore, it should be understood that various equivalents and modifications that can replace these embodiments and configurations may exist at the time of submission of this application.

[0045] According to an embodiment of the present invention, there is provided an electrode assembly comprising:

[0046] positive electrode, negative electrode and coating between the positive electrode and negative electrode,

[0047] The coating layer contains (a) oxide solid electrolyte particles and (b) one or more selected from the group consisting of polymer particles and ceramic particles.

[0048] <Coating>

[0049] The oxide-based solid electrolyte particles may include one or more selected from the group consisting of: LLTO-based compounds, Li6La2CaTa2O 12 、Li6La2ANb2O 12 (where A is Ca or Sr), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 、Li9SiAlO8、LAGP compounds、LATP compounds、Li 1+x Ti 2-x Al x Si y(PO4) 3-y (where 0≤x≤1, 0≤y≤1), LiAl x Zr 2-x (PO4)3 (where 0≤x≤1), LiTi x Zr 2-x (PO4)3 (wherein 0≤x≤1), LISICON compounds, LIPON compounds, perovskite compounds, Nasicon compounds, LLZO compounds and LLZMO compounds, and are not limited thereto, but specifically, may be LATP compounds.

[0050] Among them, the LLTO compound can be a compound containing Li, La, Ti, and O. Specifically, Li 3x La (2 / 3-x) TiO2. LAGP compounds can be compounds containing Li, Al, Ge, P, O, specifically, Li 1+x Al x Ge 2-x (PO4)3 (where 0≤x≤1). LATP compounds can contain Li, Al, Ti, P and O. Specifically, Li 1+x Al x Ti 2-x (PO4)3 (where 0≤x≤1). In addition, LIPON compounds can be compounds containing Li, P, O, and N, and LLZO compounds can be compounds containing Li, La, Zr, and O, specifically Li7La3Zr2O 12 LLZMO compounds can be compounds containing Li, La, Zr, O, M=Nb or Ta. Specifically, Li 7-x La3Zr 2-x M x O 12 (where 0≤x≤1).

[0051] When the coating layer contains oxide-based solid electrolyte particles, this is preferable because the oxide-based solid electrolyte particles themselves have an affinity for the electrolyte, thereby reducing the resistance.

[0052] The average particle size (D50) of the oxide-based solid electrolyte particles may be 50 nanometers to 10 micrometers, specifically 50 nanometers to 5 micrometers, and more specifically 50 nanometers to 1 micrometer.

[0053] If the average particle size exceeds the above range and is too small, the particles may aggregate due to reduced dispersibility. On the other hand, if the average particle size is too large, the pores of the coating may become too large, and lithium dendrites may easily form through the pores, which is not preferred.

[0054] The oxide-based solid electrolyte particles may be present in an amount of 10 wt % to 90 wt %, specifically 10 wt % to 80 wt %, and more specifically 10 wt % to 60 wt %, based on the total weight of the coating layer.

[0055] When the average particle size satisfies the above range, the lithium ion conductivity of the coating layer can be improved, thereby reducing the resistance and exhibiting improved secondary battery performance.

[0056] At the same time, the polymer particles may be particles with surface charges. Alternatively, the polymer particles may include both particles with surface charges and particles without surface charges. The surface charges may be present on the particles themselves or may be formed by physical or chemical surface treatment.

[0057] Here, the absolute value of the zeta potential of the polymer particles may be 25 mV or greater, specifically 35 mV or greater, and more specifically 45 mV or greater. When the absolute value of the zeta potential satisfies the above range, even when a flame-retardant electrolyte is applied to a lithium secondary battery containing an electrode of the present invention, the flame-retardant electrolyte can be easily impregnated into the coating, allowing a uniform reaction to occur throughout the electrode, thereby improving the performance of the lithium secondary battery, such as capacity, output, and life characteristics.

[0058] Specifically, the polymer particles may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate, but are not limited thereto. The polymer particles are different from the binder that bonds the constituent elements, but are not limited thereto, as long as they are materials that can be used as polymer-based solid electrolyte particles. Specifically, the polymer particles may include polymethyl methacrylate.

[0059] The average particle size (D50) of the polymer particles may be 50 nanometers to 3 micrometers, specifically 50 nanometers to 2 micrometers, and more specifically 50 nanometers to 1.5 micrometers.

[0060] When the average particle size (D50) of the polymer particles meets the above numerical range, the dispersibility of the particles contained in the coating can be improved, and pores of appropriate size are uniformly formed in the coating, thereby improving the mobility of lithium ions. On the other hand, when the average particle size (D50) of the polymer particles is less than 50 nanometers, due to the reduced dispersibility of the particles, aggregation occurs between the particles, and the pores are blocked by the aggregated particles, thereby reducing the mobility of lithium ions and increasing the resistance. If the average particle size (D50) of the polymer particles is greater than 3 microns, there is a problem of forming a lithium dendrite growth path as described above.

[0061] The absolute value of the zeta potential of the ceramic particles can be 25 mV or greater, specifically 35 mV or greater, and more specifically 45 mV or greater. When the absolute value of the zeta potential satisfies the above range, even when a flame-retardant electrolyte is applied to a lithium secondary battery containing the electrode of the present invention, the flame-retardant electrolyte can be easily impregnated into the coating, allowing a uniform reaction to occur throughout the electrode, thereby improving the performance of the lithium secondary battery, such as capacity, output, and lifespan.

[0062] Specifically, the ceramic particles may include one or more selected from the group consisting of boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5 and MnO, and are not limited thereto. Specifically, they may include boehmite.

[0063] The average particle size (D50) of the ceramic particles may be 30 nanometers to 5 micrometers, specifically 50 nanometers to 3 micrometers, and more specifically 50 nanometers to 1 micrometer.

[0064] When the average particle size of the ceramic particles D 50 When the average particle size is small, the particles may aggregate due to reduced dispersibility, and if the average particle size is large, there is a problem that a lithium dendrite growth path may be formed.

[0065] As used herein, the average particle size D 50 It refers to the particle size when the cumulative volume of particles in the particle size distribution curve reaches 50%. 50 The measurement can be performed using, for example, laser diffraction, which can generally measure particle sizes from the submicron range to several millimeters, and can obtain results with high reproducibility and high resolution.

[0066] Polymer particles or ceramic particles may be included alone or together.

[0067] More specifically, the coating layer may contain polymer particles and oxide-based solid electrolyte particles. That is, the coating layer may substantially contain both the oxide-based solid electrolyte particles and the polymer particles. In this case, the lithium ion transport performance is further improved.

[0068] Meanwhile, when the coating layer includes both polymer particles and ceramic particles, the mixing ratio of the polymer particles to the ceramic particles may be 3:7 to 7:3, specifically 4:6 to 6:4, by weight.

[0069] When the mixing ratio satisfies the above range, deterioration of pore uniformity, heat resistance, and electrolyte impregnation properties of the coating layer can be prevented.

[0070] Meanwhile, the coating layer may further include one or more additives selected from the group consisting of a binder and a dispersant.

[0071] At the same time, the dispersant can inhibit the excessive aggregation of polymer particles in the coating, thereby enabling the polymer particles to be effectively dispersed and present in the coating.

[0072] The dispersant may include a hydrogenated nitrile polymer. Specifically, the dispersant may be a hydrogenated nitrile copolymer, more specifically, hydrogenated nitrile butadiene rubber (H-NBR).

[0073] The hydrogenated nitrile copolymer may be a copolymer containing structural units derived from α,β-unsaturated nitrile and structural units derived from hydrogenated conjugated diene, or a copolymer containing structural units derived from α,β-unsaturated nitrile, structural units derived from conjugated diene, and structural units derived from hydrogenated conjugated diene. As the α,β-unsaturated nitrile monomer, for example, acrylonitrile, methacrylonitrile, etc. can be used, and any one of them or a mixture of two or more thereof can be used. As the conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms, such as 1,3-butadiene, isoprene, or 2,3-methylbutadiene can be used, and any one of them or a mixture of two or more thereof can be used.

[0074] The dispersant may be present in an amount of 1 to 20 wt %, specifically 1 to 15 wt %, and more specifically 1 to 10 wt %, based on the total weight of the coating. When the dispersant content satisfies the above range, the dispersibility of the particles in the coating can be improved, pores can be uniformly formed in the coating, and cracks on the coating surface can be significantly reduced.

[0075] The function of the binder is to improve the adhesion between the particles of the coating and the electrodes and separator.

[0076] Examples of the binder may include one or more selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone (PVP), polytetrafluoroethylene, polyethylene, polypropylene, EPDM rubber, sulfonated EPDM rubber, styrene-butadiene rubber, and fluororubber. Specifically, the binder may include polyvinylidene fluoride.

[0077] The binder content may be 0.1 to 20% by weight, specifically 0.5 to 15% by weight, and more specifically 1 to 10% by weight, based on the total weight of the coating. If the binder content exceeds the above range and is too low, the effect of improving adhesion cannot be expected. If the binder content is too high, the content of other particles is relatively reduced, which is not preferred.

[0078] The coating layer having the above-mentioned constitution may have electrical insulation properties. In this case, the coating layer may be equivalent to a porous insulating layer, but is not limited thereto.

[0079] The coating is resistant to shrinkage even at high temperatures. Therefore, when applied to electrode assemblies, it can prevent short circuits between the positive and negative electrodes even in high-temperature environments, thereby improving the high-temperature safety of lithium secondary batteries.

[0080] <Electrode Assembly>

[0081] Hereinafter, electrode assemblies of various structures will be described with reference to the accompanying drawings.

[0082] In one example, the coating layer may be formed on the positive electrode or the negative electrode.

[0083] Figures 1 to 3 A configuration in which a coating is formed on one side of the positive electrode or the negative electrode is shown.

[0084] Specifically, Figure 1 Schematically shows an electrode assembly having a structure in which two or more coating layers are formed on the negative electrode instead of the separator, Figure 2 An electrode assembly having a structure in which a coating layer is formed on a negative electrode and a separator is interposed between the coating layer and a positive electrode is schematically shown. Figure 3 An electrode assembly having a structure in which a coating layer is formed on a positive electrode and a separator is interposed between the coating layer and the negative electrode is schematically shown.

[0085] First, refer to Figure 1 , the electrode assembly 100 according to the embodiment of the present invention includes a negative electrode 110 , a positive electrode 120 , and a coating layer 130 .

[0086] The negative electrode 110 has a structure in which a negative electrode active material layer 112 is formed on a negative electrode current collector 111. Here, the negative electrode active material layer includes electrode materials such as a negative electrode active material, a conductive material, and a binder. In addition, although not shown in the figure, the negative electrode may be a graphite electrode made of carbon (C) or may be a metal itself.

[0087] The negative electrode current collector 111 is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or copper or stainless steel whose surface is treated with one of carbon, nickel, titanium or silver, aluminum-cadmium alloy, etc. can be used.

[0088] The thickness of the negative electrode current collector 111 can typically be 3 μm to 500 μm. Similar to the positive electrode current collector, the negative electrode current collector can have fine concave and convex surfaces to enhance adhesion of the negative electrode active material. For example, the negative electrode current collector can take various forms, such as a film, sheet, foil, mesh, porous body, foam, and non-woven fabric structure.

[0089] The negative electrode active material may include one or more selected from the group consisting of lithium metal, carbon materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of lithium and these metals, metal composite oxides, materials that can be doped and dedoped with lithium, and transition metal oxides.

[0090] As a carbon material capable of reversibly intercalating / deintercalating lithium ions, any carbon material can be used without particular limitation, as long as it is a carbon-based negative electrode active material commonly used in lithium ion secondary batteries, and as a typical example, crystalline carbon, amorphous carbon, or both can be used. Examples of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of amorphous carbon can be soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, and fired coke.

[0091] As the metal or the alloy of lithium and these metals, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn or the alloy of lithium and these metals can be used.

[0092] As the metal composite oxide, one selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1) and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups I, II and III of the periodic table or halogen; 0 <x≤1;1≤y≤3;1≤z≤8)。

[0093] Lithium-dopable and de-dopable materials can include Si, SiO x (0 < x ≤ 2), Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, and Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), and mixtures of SiO2 and one or more of them can be used. The element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0094] Transition metal oxides can include lithium-containing titanium composite oxides (LTO), vanadium oxides, lithium vanadium oxides, etc.

[0095] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 60% to 99% by weight, preferably 70% to 99% by weight, more preferably 80% to 98% by weight.

[0096] The conductive material is a component that can further improve the conductivity of the negative electrode active material. There is no particular limitation on such a conductive material as long as it has conductivity without causing chemical changes in the battery. For example, the following can be used: conductive materials such as carbon powder, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal cracking carbon black; graphite powder, such as natural graphite, artificial graphite, or graphite with a well-developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; carbon fluoride powder; conductive powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0097] Based on the total weight of the negative electrode active material layer, the content of the conductive material can be 0.1% to 10% by weight, specifically 0.5% to 5% by weight, more specifically 0.5% to 3% by weight.

[0098] The binder is a component that facilitates bonding between the conductive material, the negative electrode active material, and the negative electrode current collector. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, EPDM rubber, sulfonated EPDM rubber, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0099] Generally, the binder may be included in an amount of 0.5 to 10 wt %, specifically 0.5 to 5 wt %, and more specifically 0.5 to 3 wt %, based on the total weight of the negative active material layer.

[0100] When the metal itself is used without forming a negative electrode active material layer on the negative electrode, it can be manufactured by physically bonding, rolling or depositing the metal on the metal film itself or the negative electrode current collector. As a deposition method, metal electrodeposition or chemical vapor deposition can be used.

[0101] For example, the metal film itself or the metal bonded / rolled / deposited on the negative electrode current collector may include one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In) or an alloy of two thereof.

[0102] The positive electrode 120 has a structure in which a positive electrode active material layer 122 is formed on a positive electrode current collector 121. Here, the positive electrode active material layer includes electrode materials such as a positive electrode active material, a conductive material, and a binder.

[0103] The positive electrode current collector 121 is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, or silver can be used as the current collector.

[0104] The thickness of the positive electrode current collector 121 can typically be 3 μm to 500 μm. Fine irregularities can be formed on the entire surface of the positive electrode current collector to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector can take various forms, such as a film, sheet, foil, mesh, porous body, foam, and non-woven fabric structure.

[0105] The positive electrode active material may be a compound capable of reversibly inserting and extracting lithium, specifically, it may include a lithium metal oxide containing lithium and one or more metals (such as cobalt, manganese, nickel or aluminum). More specifically, the lithium metal oxide may include lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese ... 1-Y MnY O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc., lithium nickel cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1, etc.), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc., lithium nickel manganese cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc., or lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are atomic fractions of each independent element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, p2 + q2 + r2 + s2 = 1), etc., lithium iron phosphate (e.g., Li 1+a Fe 1-x M x (PO 4-b )X b (where M is one or more selected from Al, Mg, and Ti, X is one or more selected from F, S, and N, -0.5 ≤ a ≤ 0.5, 0 ≤ x ≤ 0.5, 0 ≤ b ≤ 0.1), etc., and any one or two or more of these compounds can be used.

[0106] Among these compounds, in terms of improving the capacity characteristics and stability of the battery, lithium metal oxides can include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxides (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2) or lithium iron phosphate (such as LiFePO4), etc., any one of which alone or a mixture of two or more can be used.

[0107] The content of the positive electrode active material may be 60 wt % to 99 wt %, preferably 70 wt % to 99 wt %, and more preferably 80 wt % to 98 wt %, based on the total weight of the positive electrode active material layer.

[0108] The descriptions of the conductive material and the binder are the same as those of the negative electrode active material layer.

[0109] At the same time, a coating layer 130 is formed between the positive electrode 120 and the negative electrode 110 .

[0110] At this time, the thickness (t) of the coating layer 130 may be 3 to 30 microns, specifically 5 to 20 microns, and more specifically 5 to 15 microns. If the thickness exceeds the above range and is too thin, the desired effect of the present application cannot be achieved, and the physical insulation between the positive electrode 120 and the negative electrode 110 cannot be fully ensured. If the thickness is too thick, the resistance may increase, which is not preferred.

[0111] The thickness (t) of the coating 130 can be easily measured using a thickness gauge or a cross-sectional SEM photograph.

[0112] Furthermore, the coating layer 130 may be formed to have a width sufficient to completely insulate the positive electrode 120 from the negative electrode 110. Specifically, when the negative electrode 110 is larger than the positive electrode 120, there is no limitation as long as its area is equal to or larger than the positive electrode 120. However, in order to facilitate the manufacturing process, the coating layer 130 may be formed to have an area corresponding to the entire area of ​​the coated object.

[0113] Figure 1The structure in which the coating layer 130 is formed on the negative electrode 110 is disclosed as an example, and in this way, the coating layer 130 can be formed to have an area corresponding to the negative electrode 110. Specifically, for example, the coating layer 130 can be formed by applying a composition for forming a coating layer on the negative electrode 110 and drying it. Alternatively, the coating layer can be formed as a self-standing film and attached to the negative electrode 110, or the coating layer can be formed by applying a composition for forming a coating layer on a substrate and drying it, and then transferring it to the negative electrode 110, and the method is not limited. Hereinafter, a method of forming a coating layer by applying a composition for forming a coating layer on an electrode or a separator and drying it will be described, but it goes without saying that the method is not limited thereto and can be formed by various methods.

[0114] Although not shown in the drawings, it goes without saying that by coating the composition for forming a coating layer on the positive electrode and drying it, a coating layer having an area corresponding to the positive electrode can be formed.

[0115] exist Figure 1 In the embodiment, the coating 130 also replaces the diaphragm to play the role of electrical insulation.

[0116] At the same time, refer to Figure 2 and Figure 3 In another exemplary embodiment, the electrode assembly has Figure 1 The structure shown further includes a membrane structure.

[0117] Specifically, refer to Figure 2 The electrode assembly 200 includes a coating layer 230 between the positive electrode 220 and the negative electrode 210 , and a separator 240 between the coating layer 230 and the positive electrode 220 .

[0118] For example, the coating layer 230 is formed by coating and drying a composition for forming a coating layer on the negative electrode 210 , and thus may be formed to have an area corresponding to the negative electrode 210 , with the separator 240 interposed between the coating layer 230 and the positive electrode 220 .

[0119] Here, the use of the separator is not particularly limited as long as it is generally used as a separator in a lithium secondary battery. In particular, a separator having high moisture retention capacity for electrolytes and low resistance to the movement of electrolyte ions is preferred.

[0120] For example, as a separator, a porous polymer film made of a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butylene copolymer), or a laminated structure of two or more layers thereof can be used. In addition, conventional porous non-woven fabrics (e.g., non-woven fabrics formed from high-melting-point glass fibers, polyethylene terephthalate fibers, etc.) can also be used as separators.

[0121] Alternatively, it may be an SRS (Safety Reinforced Separator) separator having a structure in which an organic-inorganic hybrid layer containing inorganic particles and a binder is formed on one or both surfaces of a substrate.

[0122] Specifically, the substrate of the SRS separator may be a porous polymer film containing a polyolefin-based polymer.

[0123] Inorganic particles can form gaps between them, acting as spacers for the formation of micropores while maintaining their physical shape. Since inorganic particles generally have the characteristic of not changing their physical properties even at temperatures as high as 200°C or above, the resulting organic / inorganic composite porous membrane has excellent heat resistance.

[0124] There is no particular limitation on the inorganic particles, as long as they are electrochemically stable. That is, there is no particular limitation on the inorganic particles that can be used in the present invention, as long as no oxidation and / or reduction reaction occurs within the operating voltage range of the battery in use. In particular, since inorganic particles with ion transport ability can improve ionic conductivity and promote performance improvement in electrochemical devices, inorganic particles with higher ionic conductivity are preferred. In addition, when the density of inorganic particles is high, the problem of increased weight of the manufactured battery and the problem of difficulty in dispersion during the manufacturing process are brought about. Therefore, inorganic particles with lower density may be preferred. In addition, inorganic particles with high dielectric constants can help increase the dissociation of electrolyte salts (such as lithium salts) in liquid electrolytes, thereby improving the ionic conductivity of the electrolyte. Finally, since inorganic particles with thermal conductivity have excellent heat absorption capacity, heat can be locally concentrated to form hot spots, thereby suppressing the phenomenon that causes thermal runaway, and are therefore more preferred.

[0125] For the above reasons, the inorganic particles may preferably be one or more selected from the following groups: (a) high dielectric constant inorganic particles, whose dielectric constant is greater than 1, greater than 5, and preferably greater than 10; (b) inorganic particles with piezoelectricity; (c) thermally conductive inorganic particles; (d) inorganic particles with lithium ion transport capability.

[0126] Piezoelectric inorganic particles are materials that are non-conductive under normal pressure but become conductive when their internal structure changes under a certain pressure. These materials not only possess high dielectric properties, such as a dielectric constant exceeding 100, but also generate an electric charge when pressure is applied to stretch or compress the piezoelectric material, causing one surface to become positively charged and the other negatively charged, thereby generating an electric potential between the two surfaces.

[0127] Examples of inorganic particles having piezoelectricity may include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT), PB(Mg3Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), hafnium dioxide (H f O2), or a mixture thereof, but not limited thereto.

[0128] "Inorganic particles with lithium ion transport ability" refers to inorganic particles that contain lithium atoms but have the ability to move lithium ions without storing lithium. Due to a defect in the particle structure of inorganic particles with lithium ion transport ability, lithium ions can be transported and migrated, thereby preventing the decrease in lithium mobility and further preventing the decrease in battery capacity.

[0129] Inorganic particles with lithium ion transport ability can be lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y glass, such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 (0 < x < 4, 0 < y < 13), lanthanum lithium titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), such as Li 3.25 Ge 0.25 P 0.75 S4, lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), such as Li3N, SiS2 glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), such as Li3PO4 - Li2S - SiS2, P2S5 glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), such as LiI - Li2S - P2S5 or a mixture thereof, but not limited thereto.

[0130] In addition, examples of inorganic particles having a dielectric constant of 1 or greater may be SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, or a mixture thereof, but are not limited thereto.

[0131] The thermally conductive inorganic particles are insulating materials that provide lower heat resistance but do not provide conductivity, such as one or more selected from the group consisting of aluminum nitride (AlN), boron nitride (BN), aluminum oxide (Al2O3), silicon carbide (SiC) and beryllium oxide (BeO), but are not limited thereto.

[0132] If the above-mentioned high dielectric inorganic particles, piezoelectric inorganic particles and inorganic particles having lithium ion transporting ability are used in combination, the synergistic effect can be doubled.

[0133] There is no limit to the particle size of the inorganic particles, but to ensure appropriate porosity between the inorganic particles, a particle size of 0.001 μm to 10 μm is preferred, if possible. When the particle size is less than 0.001 μm, dispersibility deteriorates, making it difficult to adjust physical properties. When the particle size is greater than 10 μm, the thickness increases, degrading mechanical properties. Furthermore, due to excessively large pores, the coating cannot fully function, increasing the likelihood of internal short circuits during battery charging and discharging.

[0134] The content of the inorganic particles is not particularly limited, but is preferably 1 to 99% by weight, particularly 10 to 95% by weight, based on 100% by weight of the mixture of the inorganic particles and the binder. If the content of the inorganic particles is less than 1% by weight, the content of the binder may be too high, and due to the reduction in the gaps formed between the inorganic particles, the pore size and porosity may be reduced, thereby reducing the mobility of lithium ions. On the other hand, when the content exceeds 99% by weight, the content of the binder is too low, the bonding force between the inorganic particles becomes weak, and the mechanical properties of the coating deteriorate.

[0135] Meanwhile, the adhesive material is not limited as long as it does not cause a side reaction with the electrolyte, and in particular, an adhesive material having a glass transition temperature (Tg) as low as possible, preferably -200°C to 200°C, can be used because the mechanical properties of the final insulating film can be improved.

[0136] Furthermore, the binder material does not necessarily need to have ion conductivity, but it is more preferable to use a polymer having ion conductivity.

[0137] Therefore, if possible, the binder material preferably has a high dielectric constant. In practice, since the degree of salt dissociation in the electrolyte depends on the dielectric constant of the electrolyte solvent, the higher the dielectric constant of the polymer, the more the degree of salt dissociation in the electrolyte can be improved. The dielectric constant of the polymer can be 1 or greater, specifically 1.0 to 100 (measurement frequency = 1 kHz), and particularly preferably 10 or greater.

[0138] In addition to the above functions, the binder material may also have the property of being able to exhibit a high degree of swelling of the electrolyte by gelation when immersed in a liquid electrolyte. When the binder material has a substantially excellent electrolyte swelling degree (or impregnation rate), the electrolyte injected after battery assembly can penetrate into the above polymer, and the polymer containing the absorbed electrolyte has electrolyte ion conductivity. Therefore, if possible, a solubility parameter of 15 MPa is preferred. 1 / 2 to 45MPa 1 / 2 polymer, 15MPa 1 / 2 to 25MPa 1 / 2 and 30MPa 1 / 2 to 45Mpa 1 / 2 More preferably, when the solubility parameter is less than 15 MPa 1 / 2 and greater than 45MPa 1 / 2 When it is thicker, it becomes difficult to be impregnated by liquid electrolytes used in conventional batteries.

[0139] Examples of the binding material include one or more selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, and polyvinyl alcohol.

[0140] The total thickness of the separator can be 5 to 20 microns, specifically 5 to 15 microns, and more specifically 6 to 13 microns. If the separator thickness meets the above range, it can effectively prevent short circuits between the positive and negative electrodes while minimizing the resistance value of the lithium secondary battery. Therefore, it is possible to prevent the energy density of the lithium secondary battery from decreasing and improve its lifespan characteristics.

[0141] Reference Figure 3 , shows an electrode assembly 300 having a structure including a coating layer 330 between a positive electrode 320 and a negative electrode 310 and a separator 340 between the coating layer 330 and the negative electrode 310 .

[0142] Since the coating layer 330 is formed by coating and drying a composition for forming a coating layer on the cathode 320 , it may be formed to have an area corresponding to the cathode 320 with the separator 340 interposed between the coating layer 330 and the anode 310 .

[0143] The description about the diaphragm 340 is the same as above.

[0144] In another embodiment, the coating layer may be formed on both the positive electrode and the negative electrode. In other words, the coating layer may be composed of a first coating layer formed on the positive electrode and a second coating layer formed on the negative electrode.

[0145] Figures 4 and 5 A configuration in which coatings are formed on both the positive electrode and the negative electrode is disclosed.

[0146] Specifically, Figure 4 An electrode assembly is schematically shown in which coatings are formed on the positive electrode and the negative electrode instead of the separator. Figure 5 An electrode assembly having a structure in which a separator is interposed between coating layers is schematically shown.

[0147] Reference Figure 4 , the electrode assembly 400 is formed with a structure such that the coating layer 431 formed on the negative electrode 410 and the coating layer 432 formed on the positive electrode 420 are in contact with each other.

[0148] That is, the coating layers 431 and 432 are located between the negative electrode 410 and the positive electrode 420 instead of the separator, and the coating layers 431 and 432 play a role of electrical insulation.

[0149] Here, the coating layer 431 is formed by coating the composition for forming a coating layer on the negative electrode 410 and drying it, and thus may have an area corresponding to the negative electrode 410 . The coating layer 432 is formed by coating the composition for forming a coating layer on the positive electrode 410 and drying it, and thus may have an area corresponding to the positive electrode 420 .

[0150] Meanwhile, when thus formed on both electrodes, the coating layers 431 and 432 may have thicknesses t2 and t1 of 3 to 30 μm, respectively, specifically, 5 to 20 μm, and more specifically, 5 to 15 μm.

[0151] In addition, the total thickness (t1+t2) may be 10 μm to 50 μm, specifically 10 μm to 30 μm.

[0152] Also, see Figure 5 In another example, the electrode assembly 500 has Figure 4 The structure shown also includes the structure of the diaphragm 540.

[0153] Specifically, see Figure 5The electrode assembly 500 has a structure in which coating layers 531 and 532 are formed on the negative electrode 510 and the positive electrode 520 , respectively, and includes a separator 540 located between the coating layers 531 and 532 .

[0154] As described above, the coating layer 531 is formed by applying a composition for forming a coating layer on the negative electrode 510 and drying it, and thus, can be formed to have an area corresponding to the negative electrode 510, while the coating layer 532 is formed by applying a composition for forming a coating layer on the positive electrode 520 and drying it, and thus, can be formed to have an area corresponding to the positive electrode 520.

[0155] The diaphragm 540 is as described above.

[0156] In another example, the electrode assembly may include a separator, and the coating layer may have a structure formed on one side or both sides of the separator.

[0157] Figure 6 Disclosed is a structure for forming a coating layer on a separator.

[0158] Specifically, see Figure 6 , coatings 631 and 632 are located between the negative electrode 610 and the positive electrode 620, and the coatings 631 and 632 are formed on both sides of the separator 640. Although not shown in the figure, it is self-evident that they can be formed on only one side of the separator, for example, the side facing the positive electrode 620 or the side facing the negative electrode 610.

[0159] The coating layers 631 and 632 are formed by applying a composition for forming a coating layer on both surfaces of the diaphragm 640 and drying the composition, and thus, the coating layers 631 and 632 may be formed to have an area corresponding to the area of ​​the diaphragm 640 .

[0160] When the coating layers 631 and 632 are formed on both sides of the diaphragm 640 in this manner, the thicknesses t4 and t3 thereof may be 2 to 30 micrometers, more specifically 2 to 15 micrometers, and more specifically 2 to 10 micrometers.

[0161] In addition, the total thickness t3 + t4 may be 4 micrometers to 50 micrometers, specifically 4 micrometers to 20 micrometers.

[0162] <Lithium Secondary Battery>

[0163] Hereinafter, the lithium secondary battery of the present invention will be described.

[0164] The lithium secondary battery of the present invention may include the electrode assembly, an electrolyte, and a battery case.

[0165] The electrolyte may be a non-aqueous lithium electrolyte containing a non-aqueous organic solvent and a lithium salt, or may be a flame-retardant electrolyte containing a flame-retardant solvent and a lithium salt.

[0166] As the non-aqueous organic solvent for the non-aqueous lithium electrolyte, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxane, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc. can be used.

[0167] However, when non-aqueous lithium electrolytes contain such non-aqueous organic solvents, they are volatile, flammable, and potentially lead to battery safety issues. Therefore, the electrolyte may be a flame-retardant electrolyte.

[0168] The flame-retardant electrolyte is an electrolyte that is not easily volatile and does not catch fire. Therefore, when the flame-retardant electrolyte is applied to lithium secondary batteries, the high-temperature safety of the battery can be ensured.

[0169] Meanwhile, flame-retardant electrolytes have the problem of reducing the impregnation property of lithium secondary battery separators (eg, polyolefin separators). However, the coating of the present invention can improve the impregnation property of the flame-retardant electrolyte, thereby enabling the use of the flame-retardant electrolyte.

[0170] Here, the flame retardant solvent can serve as a medium through which ions participating in the electrochemical reaction of the battery can move. For example, the flame retardant solvent can include one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds, and fluorocarbonate compounds.

[0171] The sulfone compound can be a cyclic sulfone compound or a linear sulfone compound, specifically, it can include one or more compounds selected from the group consisting of cyclopentane sulfone, tetramethylene sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-isopropyl sulfone, ethyl-isobutyl sulfone, isopropyl-isobutyl sulfone, isopropyl-sec-butyl sulfone, and butyl-isobutyl sulfone.

[0172] The nitrile compound may include one or more compounds selected from the group consisting of acetonitrile, succinonitrile, adiponitrile, malononitrile, glutaronitrile, suberonitrile, and sebaconitrile.

[0173] The phosphoric acid compound may include one or more compounds selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethyl phosphate, dimethyl methyl phosphate, dimethyl (2-methoxyethoxy)methylphosphonate, diethyl (2-methoxyethoxy)methylphosphonate, and triphenyl phosphate.

[0174] Fluorinated carbonate compounds may include one or more compounds selected from the group consisting of bis(2,2,3,3-tetrafluoropropyl) carbonate, methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, propyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, ethyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-isopropyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolane-2-one and bis(2,2,3,3-pentafluoropropyl) carbonate.

[0175] Lithium salts are used as media for transporting ions in lithium secondary batteries. Lithium salts may include, for example, Li + as a cation, and may contain one or more selected from the group consisting of: F - 、Cl - Br - , I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 -、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .

[0176] Specifically, the lithium salt may include a lithium salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2) or a mixture of two or more thereof, however, from the perspective of excellent stability, it is preferred to contain LiN(SO2CF3)2.

[0177] In addition, lithium salts commonly used in lithium secondary battery electrolytes may also be used without particular limitation.

[0178] The concentration of the lithium salt can be appropriately changed within a generally applicable range, but in order to obtain the best effect of forming a corrosion-preventing film on the electrode surface, the concentration of the lithium salt contained in the electrolyte can be 1 M to 3 M, specifically 1 M to 2.5 M, and more specifically 1 M to 2 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics of the lithium secondary battery during high-temperature storage is sufficient, the viscosity of the flame-retardant electrolyte is appropriate, and thus the impregnation property of the flame-retardant electrolyte can be improved.

[0179] In addition, in order to improve the charge and discharge characteristics, flame retardancy, etc., the electrolyte may further contain pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, a halogen-containing solvent such as carbon tetrachloride and trifluoroethylene may be further added to impart non-flammability, carbon dioxide gas may be further included to improve high-temperature storage characteristics, and FEC (fluoroethylene carbonate) and PRS (propylene sultone) may be further included.

[0180] The lithium secondary battery of the present invention may be manufactured by housing an electrode assembly together with an electrolyte in a battery case.

[0181] The battery case may be a commonly used battery case in the art, and its outer shape is not limited depending on the battery application, for example, it may be cylindrical, prismatic, pouch-shaped or coin-shaped, but is not limited thereto.

[0182] The lithium secondary battery of another embodiment of the present invention can be used not only as a battery cell for powering small devices, but is also preferably used as a unit cell for large and medium-sized battery modules containing multiple battery cells. Preferred examples of large and medium-sized devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).

[0183] Hereinafter, the present invention will be described in detail with reference to specific examples. However, the following examples are merely exemplary embodiments for ease of understanding of the present invention and are not intended to limit the scope of the present invention. It will be apparent to those skilled in the art that various changes and modifications may be made to the present invention without departing from the scope and spirit of the present invention, and it goes without saying that such changes and modifications are also within the scope of the appended claims.

[0184] <Example 1>

[0185] Preparation of composition for forming coating

[0186] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 μm), boehmite (D50: 0.35 μm, zeta potential: 35 mV), polymethyl methacrylate (PMMA) polymer particles (D50: 1 μm, zeta potential: -50 mV), hydrogenated nitrile rubber (H-NBR) and polyvinylidene fluoride (PVDF) are placed and dispersed in N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 60:10:10:5:15 to prepare a composition for forming a coating.

[0187] The particle size D was measured by measuring the particle size value at 50% cumulative volume using laser diffraction. 50 The zeta potential values ​​were measured using an electrophoretic light scattering method using a dynamic light scattering apparatus.

[0188] Anode manufacturing

[0189] Next, a copper (Cu) metal film with a thickness of 20 microns was prepared as a negative electrode current collector, and graphite as a negative electrode active material, carbon black as a conductive material, carboxymethyl cellulose (CMC) as a thickener, and PVDF as a binder were placed and dispersed in water at a weight ratio of 95:1:1.5:2.5. The prepared negative electrode slurry was coated on one side of the copper metal film, dried, and rolled to a thickness of 75 microns to manufacture a negative electrode.

[0190] Cathode manufacturing

[0191] Prepare an aluminum (Al) metal film with a thickness of 15 μm as the positive electrode current collector, and use Li (Ni 0.8 Mn 0.1 Co 0.1 )O2, carbon nanotubes as a conductive material, and PVDF as a binder are placed and dispersed in an NMP solvent in a weight ratio of 96:1:3. The prepared positive electrode slurry is coated on one side of an aluminum metal film, dried, and rolled to a thickness of 60 μm to manufacture a positive electrode.

[0192] Manufacturing of electrode assemblies

[0193] The composition for forming a coating layer was coated on the negative electrode active material layer of the negative electrode to a thickness of 30 μm and dried to form a coating layer.

[0194] Then, if Figure 1 As shown, the electrode assembly is manufactured by placing the coating layer and the positive electrode active material layer of the positive electrode in contact with each other.

[0195] Manufacturing of lithium secondary batteries

[0196] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and housed in a battery case to manufacture a lithium secondary battery.

[0197] <Example 2>

[0198] In the same manner as in Example 1, a composition for forming a coating layer, a positive electrode, and a negative electrode were manufactured.

[0199] Manufacturing of electrode assemblies

[0200] The composition for forming a coating layer was coated on the negative electrode active material layer of the negative electrode to a thickness of 20 μm and dried to form a coating layer.

[0201] The composition for forming a coating layer was coated on the positive electrode active material layer of the positive electrode to a thickness of 20 μm and dried to form a coating layer.

[0202] Then, if Figure 4 As shown, the electrode assembly is manufactured by placing a coating layer of a negative electrode and a coating layer of a positive electrode in contact with each other.

[0203] Manufacturing of lithium secondary batteries

[0204] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and housed in a battery case to manufacture a lithium secondary battery.

[0205] <Example 3>

[0206] In the same manner as in Example 1, a composition for forming a coating layer, a positive electrode, and a negative electrode were manufactured.

[0207] Manufacturing of electrode assemblies

[0208] The composition for forming a coating layer was coated on the positive electrode active material layer of the positive electrode to a thickness of 20 μm and dried to form a coating layer.

[0209] Then, if Figure 3 As shown, the coating layer of the positive electrode and the negative electrode active material layer of the negative electrode were arranged to face each other, and a separator made of polyolefin (thickness: 15 μm) was arranged to be interposed therebetween, thereby manufacturing an electrode assembly.

[0210] Manufacturing of lithium secondary batteries

[0211] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and housed in a battery case to manufacture a lithium secondary battery.

[0212] <Example 4>

[0213] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 3, except that an electrolyte in which LiPF6 was dissolved in an organic solvent (ethylene carbonate:ethyl methyl carbonate=30:70 volume ratio) at 1 M was used when manufacturing the lithium secondary battery.

[0214] <Example 5>

[0215] In the same manner as in Example 1, a composition for forming a coating layer, a positive electrode, and a negative electrode were manufactured.

[0216] Manufacturing of electrode assemblies

[0217] The composition for forming a coating layer was applied to both surfaces of a polyolefin separator (thickness: 10 μm) to a thickness of 10 μm, and dried to form a coating layer.

[0218] Then, if Figure 6 As shown, an electrode assembly is manufactured by placing a coating layer, a positive electrode active material layer of a positive electrode, and a negative electrode active material layer of a negative electrode in contact with each other.

[0219] Manufacturing of lithium secondary batteries

[0220] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and housed in a battery case to manufacture a lithium secondary battery.

[0221] <Example 6>

[0222] Preparation of composition for forming coating

[0223] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 μm), boehmite (D50: 0.35 μm, zeta potential: 35 mV) and polyvinylidene fluoride (PVDF) were put into and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 60:25:15 to prepare a composition for forming a coating.

[0224] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming a coating layer was used.

[0225] <Example 7>

[0226] Preparation of composition for forming coating

[0227] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 μm), polymethyl methacrylate (PMMA) polymer particles (D50: 1 μm, zeta potential: -50 mV), hydrogenated nitrile rubber (H-NBR) and polyvinylidene fluoride (PVDF) were placed and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 60:20:5:15 to prepare a composition for forming a coating.

[0228] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming a coating layer was used.

[0229] <Example 8>

[0230] Preparation of composition for forming coating

[0231] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 μm), boehmite (D50: 0.35 μm, zeta potential: 35 mV), polymethyl methacrylate (PMMA) polymer particles (D50: 1 μm, zeta potential: -50 mV), hydrogenated nitrile rubber (H-NBR) and polyvinylidene fluoride (PVDF) were placed and dispersed in N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 10:60:10:5:15 to prepare a composition for forming a coating.

[0232] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming a coating layer was used.

[0233] <Comparative Example 1>

[0234] The positive electrode and the negative electrode were manufactured in the same manner as in Example 1.

[0235] Manufacturing of electrode assemblies

[0236] The positive electrode active material layer of the positive electrode was placed facing the negative electrode active material layer of the negative electrode, and a polyolefin separator (thickness: 15 micrometers) was placed interposed therebetween. The manufacturing method of the electrode assembly was the same as that of a general lithium secondary battery.

[0237] Manufacturing of lithium secondary batteries

[0238] The electrode assembly was impregnated with an electrolyte prepared by dissolving LiPF 6 at 1 M in an organic solvent (ethylene carbonate:ethyl methyl carbonate=30:70 volume ratio) and housed in a battery case to produce a lithium secondary battery.

[0239] <Comparative Example 2>

[0240] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Comparative Example 1, except that in Comparative Example 1, an electrolyte in which LiN(SO 2 CF 3 ) 2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, was used when manufacturing the lithium secondary battery.

[0241] <Comparative Example 3>

[0242] The positive electrode and the negative electrode were manufactured in the same manner as in Example 1.

[0243] Preparation of composition for forming coating

[0244] Al 2 O 3 (D50: 1 μm, zeta potential: −20 mV) and polyvinylidene fluoride (PVDF) were put into and dispersed in an NMP solvent at a weight ratio of 85:15 to prepare a composition for forming a coating layer.

[0245] Manufacturing of electrode assemblies

[0246] The composition for forming a coating layer was coated on the negative electrode active material layer of the negative electrode to a thickness of 20 μm and dried to form a coating layer.

[0247] The composition for forming a coating layer was coated on the positive electrode active material layer of the positive electrode to a thickness of 20 μm and dried to form a coating layer.

[0248] Subsequently, an electrode assembly is manufactured by placing the coating layer of the negative electrode and the coating layer of the positive electrode in contact with each other.

[0249] Manufacturing of lithium secondary batteries

[0250] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and housed in a battery case to manufacture a lithium secondary battery.

[0251] <Comparative Example 4>

[0252] Boehmite (D50: 0.35 μm, zeta potential: 35 mV), Al2O3 (D50: 1 μm, zeta potential: -20 mV) and polyvinylidene fluoride (PVDF) were put into and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 10:75:15 to prepare a composition for forming a coating.

[0253] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming a coating layer was used.

[0254] <Experimental Example 1>

[0255] The lithium secondary batteries of Examples 1 to 5 and Comparative Examples 1 and 2 were subjected to a hot box test.

[0256] The hot box test was performed as follows: starting from 25°C, the temperature was increased at 5°C / min, maintained at 100°C, 120°C, 140°C, 150°C, 160°C, 170°C and 180°C for 30 minutes each, and then increased to 200°C at 2°C / min.

[0257] The temperatures at which the fire started are shown in Table 1 below.

[0258] [Table 1]

[0259]

[0260] With reference to Table 1, it can be confirmed that the thermal stability of the lithium secondary battery of the present invention is more excellent, and when a flame retardant electrolyte is used, further improved thermal stability can be obtained.

[0261] Meanwhile, in the hot box test used for thermal stability comparison, since the closer the lithium secondary battery's state of charge is to full charge, the lower its thermal stability, the comparison must be made at the same full charge state. However, in the lithium secondary battery of Comparative Example 3, the electrolyte could not be impregnated with a flame-retardant solvent from the outset, making it impossible to fully charge the battery and difficult to compare thermal stability under the same conditions. Therefore, this was omitted from the corresponding evaluation results.

[0262] <Experimental Example 2>

[0263] The initial capacity and capacity retention rate of each of the lithium secondary batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were measured, and the results are shown in Table 2 below.

[0264] Each of the prepared lithium secondary batteries was charged to 4.2 V at a constant current of 0.33 C at 25° C. and discharged to 3.0 V at a constant current of 0.33 C as one cycle. After 200 charge and discharge cycles, the capacity retention rate was calculated as the ratio of the capacity after 200 cycles to the initial capacity.

[0265] [Table 2]

[0266] Initial capacity (Ah) Capacity retention rate (%) Example 1 1.92 91 Example 2 1.95 93 Example 3 1.97 97 Example 4 2.01 97 Example 5 1.98 97 Example 6 1.92 93 Example 7 1.90 92 Example 8 1.92 93 Comparative Example 1 2.02 97 Comparative Example 2 1.98 56 Comparative Example 3 1.36 62 Comparative Example 4 1.97 77

[0267] Referring to Table 2, it can be confirmed that the performance of the lithium secondary battery of the present invention is superior to that of Comparative Examples 2 to 4. This is because when a flame retardant solvent is used, the oxide solid electrolyte particles as the electrolyte increase the mobility of lithium ions, thereby enhancing the mobility of the polymer particles and improving the impregnation of the electrolyte.

[0268] It will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the spirit or scope of the inventions.

[0269] [Industrial Applicability]

[0270] The electrode assembly of the present invention is constructed such that a coating is located between the positive electrode and the negative electrode, and the coating contains one or more selected from the group consisting of polymer particles and ceramic particles and oxide solid electrolyte particles, thereby effectively maintaining the insulation between the positive electrode and the negative electrode through the coating that is not easy to shrink even in a high-temperature environment, providing an effect of improving high-temperature safety.

[0271] In addition, since the coating of the present invention itself has electrical insulation properties, it can not only act as a diaphragm in the absence of a diaphragm, but also prevent the diaphragm from shrinking when used with a diaphragm, further improving the electrical insulation properties, having heat resistance, and being more effective in high-temperature safety.

[0272] Furthermore, the coating of the present invention uses oxide-based solid electrolyte particles, so even if the electrolyte impregnation degree is slightly low, it can still serve as an electrolyte between the positive electrode and the negative electrode, thereby improving the resistance increase phenomenon of the lithium secondary battery.

[0273] Furthermore, the coating layer of the present invention can exhibit further improved effects when it contains polymer particles that can serve as polymer-based solid electrolyte particles and oxide-based solid electrolyte particles.

[0274] In addition, when used as an electrolyte together with a flame retardant electrolyte, not only is safety further improved by suppressing fire, but the problem of electrolyte impregnation degradation that may occur due to the flame retardant electrolyte can also be solved by the coating of the above-mentioned present invention, thereby having the effect of improving the performance of the lithium secondary battery despite the use of the flame retardant electrolyte.

Claims

1. An electrode assembly, comprising: A positive electrode, a negative electrode and a coating between the positive electrode and the negative electrode, in, The coating layer contains (a) oxide-based solid electrolyte particles and (b) one or more selected from the group consisting of polymer particles and ceramic particles.

2. The electrode assembly according to claim 1, wherein: The oxide solid electrolyte particles include one or more selected from the group consisting of: LLTO compounds, Li6La2CaTa2O 12 、Li6La2ANb2O 12 (where A is Ca or Sr), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x Si y (PO4) 3-y (where 0≤x≤1, 0≤y≤1), LiAl x Zr 2-x (PO4)3 (where 0≤x≤1), LiTi x Zr 2-x (PO4)3 (wherein 0≤x≤1), LISICON compounds, LIPON compounds, perovskite compounds, Nasicon compounds, LLZO compounds and LLZMO compounds.

3. The electrode assembly according to claim 1, wherein: The absolute values ​​of the zeta potentials of the polymer particles and the ceramic particles are respectively greater than 25 mV.

4. The electrode assembly according to claim 1, wherein: The polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

5. The electrode assembly according to claim 1, wherein: The ceramic particles include one or more selected from the group consisting of boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5 and MnO.

6. The electrode assembly according to claim 1, wherein: The content of the oxide-based solid electrolyte particles is 10 wt % to 90 wt % based on the total weight of the coating layer.

7. The electrode assembly according to claim 1, wherein: The coating comprises (a) oxide solid electrolyte particles and (b) polymer particles, wherein the polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

8. The electrode assembly according to claim 1, wherein: The coating further comprises one or more additives selected from the group consisting of a binder and a dispersant.

9. The electrode assembly according to claim 1, wherein: The coating has a thickness of 3 micrometers to 30 micrometers.

10. The electrode assembly according to claim 1, wherein: The coating layer is formed on the positive electrode or the negative electrode.

11. The electrode assembly according to claim 10, wherein: The electrode assembly further includes a separator, wherein the separator is located between the positive electrode and the coating layer, or between the negative electrode and the coating layer.

12. The electrode assembly according to claim 1, wherein: The coating layer includes a first coating layer formed on the positive electrode and a second coating layer formed on the negative electrode.

13. The electrode assembly according to claim 12, wherein: The electrode assembly further includes a separator, wherein the separator is located between the first coating layer and the second coating layer.

14. The electrode assembly according to claim 1, wherein: The electrode assembly further includes a separator, and the coating is formed on one side or both sides of the separator.

15. The electrode assembly according to any one of claims 12, 14 and 15, wherein: The separator is an SRS separator having a structure in which an organic-inorganic hybrid layer containing inorganic particles and a binding material is formed on one side or both sides of a substrate. 16 . A lithium secondary battery comprising the electrode assembly according to claim 1 , an electrolyte and a battery case.

17. The lithium secondary battery according to claim 16, wherein: The electrolyte is a flame retardant electrolyte containing a flame retardant solvent and a lithium salt.

18. The lithium secondary battery according to claim 17, wherein: The flame retardant solvent includes one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorocarbonate compounds.

19. The lithium secondary battery according to claim 17, wherein: The lithium salt includes LiN(SO2CF3)2.